Multivariate Analysis and Validation of the Prognostic Factors for Skull Base Chordoma - Teng, Chubei; Yang, Qi; Xiong, Zujian; Ye, Ningrong; Li, Xuejun (Frontiers in Surgery, 2021)
-Background: Skull base chordoma is a rare tumor with low-grade malignancy and high recurrence rate, the factors affecting prognosis of patients need to be further studied. For that, we investigated prognostic factors of skull base chordoma through the database of the Surveillance, Epidemiology, and End Results (SEER), and validated in an independent dataset from Xiangya Hospital. -Methods: Six hundred and forty-three patients that diagnosed as skull base chordoma were obtained from the SEER database (606 patients) and Xiangya Hospital (37 patients). Categorical variables were selected by chi-squared test with statistical difference. Survival curves were constructed by Kaplan-Meier analysis and compared by log-rank test. Univariate and multivariate Cox regression analyses were used to explore the prognostic factors. Propensity score matching (PSM) analysis was undertaken to reduce the substantial bias between Gross Total Resection (GTR) and Subtotal Resection (STR) groups. Furthermore, clinical data of 37 patients from Xiangya Hospital were used as validation cohort to check into the survival impacts of extent of resection and adjuvant radiotherapy on prognosis. -Results: We found that age at diagnosis, primary site, disease stage, surgical treatment, and tumor size were significantly associated with the prognosis of skull base chordoma. PSM analysis revealed that there was no significant difference of the OS between GTR and STR (p=0.157). Independent dataset from Xiangya Hospital proved no statistically difference in OS between GTR and STR groups (p=0.16), but GTR group was superior to the STR group for Progression-free survival (PFS) (p=0.048). Postoperative radiotherapy does not improve OS (p=0.28), but it can prolong PFS (p=0.0037). Nomograms predicting 5-year and 10-year OS and DSS were constructed based on statistically significant factors identified by multivariate Cox analysis. Age, primary site, tumor size, surgical treatment, and disease stage were included as prognostic predictors in the nomograms with good performance. -Conclusions: We identified age, tumor size, surgery, primary site and tumor stage as main factors affecting the prognosis of the skull base chordoma. Resection of tumor as much as possible while ensuring safety, combined with postoperative radiotherapy may be the optimum treatment for skull base chordoma.